PENGARUH PELAKSANAAN QR BARCODE MY PERTAMINA TERHADAP PENJUALAN BBM - Chantika, Elmi; Gustini, Gustini; Charolina, Ovita (Jurnal Adminitrasi Bisnis Nusantara, 2024)
The formulation of the problem in this research is How is the My Pertamina QR barcode implemented at SPBU 24.381.01 Kampung Kelawi, Sungai Serut District, Bengkulu City? How are fuel sales at gas station 24.381.01 Kelawi Village, Sungai Serut District, Bengkulu City? Is there an influence of the implementation of the My Pertamina QR Barcode on fuel sales at SPBU 24.381.01 Kampung Kelawi, Sungai Serut District, Bengkulu City? How much influence does the implementation of the My Pertamina QR Barcode have on fuel sales at SPBU 24.381.01 Kampung Kelawi, Sungai Serut District, Bengkulu City? The aim of this research is to determine the implementation of the My Pertamina QR barcode at SPBU 24.381.01 Kampung Kelawi, Sungai Serut District, Bengkulu City. To find out fuel sales at gas station 24,381.01 Kampung Kelawi, Sungai Serut District, Bengkulu City. To determine the magnitude of the influence of the implementation of the My Pertamina QR Barcode on fuel sales at SPBU 24.381.01 Kampung Kelawi, Sungai Serut District, Bengkulu City. Sampling in this study used a total sampling technique, namely all employees of SPBU 24.381.01 Kampung Kelawi, Sungai Serut District, Bengkulu City. Data collection methods include observational studies, questionnaires, documentation and literature. Data analysis techniques using simple linear regression, correlation coefficient, hypothesis. The research results showed that the implementation of the My Pertamina QR Barcode at SPBU 24.381.01 Kelawi Village, Sungai Serut District, Bengkulu City was included in the very good category. Fuel sales at gas station 24.381.01 Kelawi Village, Sungai Serut District, Bengkulu City are included in the very good category and are already included in the very good category. The implementation of QR Barcodes affects fuel sales at gas station 24.381.01 Kelawi Village, Sungai Serut District, Bengkulu City. The influence of the implementation of QR Barcodes on fuel sales was 88,9%, while the remaining 11,1% was explained by other factors outside the model.